Continuous insulation strategy of organic waste composting in cold region: Based on cold-adapted consortium. (September 2021) - Xie, Xinyu; Wang, Yihan; Wei, Zimin; Zhang, Yutong; Zhang, Chuang; Zhang, Shubo; Yang, Hongyu; Zhang, Xu; Zhao, Yue
Graphical abstract: Highlights: Biofortification can accelerate the heat generation during composting. A strategy for sustainable heat supplied from composting system. Ensures normal operation of composting at low temperature. Thermal energy is a clean energy source. Abstract: Compost is a self-heating process for organic waste. Microbes are the main executors in composting process. However, due to low temperature in winter and low efficiency of composting, a lot of heat is lost in composting. In this study, taking-out and feed-batch composting method (TFC) can supplement nutrition and improve composting microenvironment. Compared with NC, the amount of carbohydrates, protein and fat decomposed by TFC increase by 56.8%, 237% and 122%, respectively, in the composting start-up period (0–100 h). Structure and function of microbial community have changed due to stimulation of cold-adapted consortium. In addition, this study shows that core bacteria stimulate cooperation among different bacteria in the organic components metabolism networks. Finally, based on the important role of cold-adapted consortium, the sustainable heating strategy of composting system is put forward, which converts organic wastes into released heat for daily heating and hot water preparation, leading role of cold-adapted consortium.